قاعدة" اقتضاء النهي الفساد و البطلان " عند المذاهب الأربعة " و تطبيقاتها في المناكحات - Suranto Suranto; Imron Rosyadi; Muinudinillah Basri (Profetika: Jurnal Studi Islam, 2020)
This research is motivated by the curiosity of the law of marriage of a pregnant adulter to cover up her shame and family disgrace, which sometimes occurs in the community, while the Prophet Muhammad “peace be upon him” has forbidden men to marry a pregnant woman until she gives birth.And many other forbidden marriages that occur in the community. The formulation of the problems of this research are: 1) What are the opinions of the four ideology of thought towards the rule of "iqtidhou annahyi alfasad wal butlan"? 2) How is the application of this rule in prohibited marriages, such as marriages of men with adulterers who are pregnant, mut'ah marriages, marriages of men who have been proposed by other men, marriages in ihrom conditions, syigor marriages, bid'iy marriages, marriages without marriages proxy, marriage without witnesses, marriage by combining women who still have mahrom relations. This research was conducted by the literature review method, collecting and studying various references, especially from the four ideology of thought, then conducting in-depth analysis. The conclusions of this study are 1) the four ideology of thought differ on the the rule of "iqtidhou annahyi alfasad wal butlan" in some circumstances annahyu, and have the same view of this Qoidah in several circumstances annahyu. 2) In applying this rule in the case of marriage, they agree on its validity or sleaze in some marital matters, but also differing opinions in several other issues. Usually, their opinions on the issue of marriage are in line with their opinions on the issue of the rule of ushul, but sometimes they don’t.Penelitian ini dilatarbelakangi keingintahuan hukum nikahnya pezina yang hamil untuk menutupi aibnya dan aib keluarganya, yang kadang terjadi di masyarakat, sedangkan Nabi Muhammad Sholallohu ‘alaihi wa salam telah melarang lelaki untuk menikahi perempuan yang hamil sampai dia melahirkan. Dan banyak pernikahan-pernikahan terlarang lainya yang terjadi di masyarakat. Rumusan masalah dari penelitian ini adalah: 1) Apa pendapat empat madzhab terhadap qoidah “ iqtidhou annahyi alfasad wal butlan”? 2) Bagaimana penerapan qoidah ini dalam masalah pernikahan yang terlarang, seperti nikahnya lelaki dengan pezina yang hamil, nikah mut’ah, nikahnya lelaki atas perempuan yang sudah dilamar lelaki lain, nikah dalam kondisi ihrom, nikah syigor, tholak bid’iy, nikah tanpa wali, nikah tanpa saksi, nikah dengan menggabungkan perempuan yang masih ada hubungan mahrom. Penelitian ini dilakukan dengan metode kajian pustaka, dengan mengumpulkan dan mentelaah berbagai referensi terutama dari empat madzhab, dan menganalisanya. Kesimpulan dari hasil penelitian ini adalah 1) empatmadzhab berbeda pendapat tentang qoidah “ iqtidhou annahyi alfasad wal butlan” di beberapa keadaan annahyu, dan sama pandanganya tentang kaidah ini dalam beberapa keadaan annahyu. 2) Dalam penerapan qoidah ini dalam masalah pernikahan, mereka sepakat tentang keabsahanya atau kebatilanya dalam beberapa masalah pernikahan, dan kadang mereka juga berbeda pendapat dalam beberapa masalah lainya. Biasanya pendapat mereka dalam masalah pernikahan ini selaras dengan pendapat mereka dalam masalah qoidah ushul tersebut, tapi kadang tidak selaras. الملخص: قاعدة" اقتضاء النهي الفساد و البطلان " عند المذاهب الأربعة و تطبيقاتها في المناكحات، رسالة مقدمة لاستيفاء أحد الشروط للحصول على درجة الماجستير في تخصص الفقه و أصوله، إعداد الطالب: سورا تنو، رقم القيد:O200170020  تحت إشراف: د.عمران رشادي و د.معين دين الله بصري، عام:1441 ه / 2019م. قامت فكرة البحث على معرفة حكم نكاح الحامل بسبب الزنى لستر عيبها و عيب عائلتها الواقع في المجتمع ، مع أن النبي – صلى الله عليه و سلم – نهى عن نكاح الحامل حتى تلد كي لا يختلط النسب. قد وقعت الأنكحة الممنوعة الأخرى في المجتمع. تدور مشكلة البحث حول الأمرين التاليين: 1) ما أقوال المذاهب الأربعة في قاعدة " اقتضاء النهي الفساد و البطلان"؟ 2)كيف تطبيق هذه القاعدة  في مسائل المناكحات؟ اتّبع الباحث في هذه الرسالة البحث المكتبي، و ينهج هذا البحث منهج استقرائي و تحليلي. و توصل الباحث إلى النتائج الآتية: 1) اختلف المذاهب الأربعة في القاعدة الأصولية " اقتضاء النهي الفساد و البطلان " في بعض أحوال النهي، و اتفق في بعضها. 2) تطبيقات هذه القاعدة في المناكحات المنهي عنها في نكاح الزانية الحامل، نكاح المتعة، الخطبة على الخطبة، نكاح المحرم، نكاح الشغار، الطلاق البدعي، النكاح بدون ولي، النكاح بدون الشهود، الجمع بين المحارم في النكاح، اتفق المذاهب الأربعة على صحة بعضها أو فساده، و اختلفوا في بعضها، غالبا أن رأيهم موافق لرأيهم في القاعدة " اقتضاء النهي الفساد و البطلان"، و أحيانا مخالف لرأيهم في هذه القاعدة.